Multiorganizational arrangements for watershed protection : working better together - McNamara, Madeleine Wright; Morris, John C. (John Charles), 1959- (New York, NY : Routledge, 2021)
"With cross-pollination of the public administration and policy implementation literatures, Madeleine Wright McNamara and John Charles Morris present the Multiorganizational Interaction Model as a framework to explore the use of cooperation, coordination, and collaboration between 15 federal/state agencies, local governments, and nongovernmental organizations working together to restore coastal habitats and replenish aquatic resources on Virginia's Eastern Shore. Content analysis of data collected through interviews and organizational documents allows comparisons to be made regarding the distribution of data across the continuum of interaction. The presence of policy mandates intending to prescribe relationships coupled with strong perceptions of collaboration, create opportunity to explore mandated and voluntary collaboration. Themes regarding mapping relationships within the multiorganizational arrangement, movement on the continuum, and implementation through mid-level personnel are discussed. The combination of theory development and testing provides readers with a theoretical framework through which to think about interorganizational interactions, and a case study to illustrate the ways in which these complex relationships manifest themselves in practice. Multiorganizational Arrangements for Watershed Protection will be essential for scholars, students, and policy makers"--
Multiorganizational interactions for watershed protection -- The multiorganizational interaction model -- An empirical test of the MIM -- Perceptions of administrators implementing coastal resilience policies -- Implications for theory and practice.
OCLC-licensed vendor bibliographic record.
Keywords: Watershed management -- Political aspects -- Eastern Shore (Md. and Va.); Watershed restoration -- Political aspects -- Eastern Shore (Md. and Va.); Intergovernmental cooperation -- United States; Interagency coordination -- United States; Public-private sector cooperation -- United States; POLITICAL SCIENCE / Public Affairs & Administration; POLITICAL SCIENCE / Public Policy / Environmental Policy